O paradigmă îmbunătățită de analiză a familiilor cu copii - Urse, Laureana (Calitatea Vieții, 2007)
Most o the analyses on families with children are done in terms of economic resources, and their purpose is to identify solutions for their support. I consider it necessary to complete the analysis modalities of the families with children, in terms of: – parallel analysis between the children needs and between needs and aspirations their parents’, as well as of the patterns of relations between the parents roles – woman/ man roles – occupational/ professional roles and the other roles the parents have to play; – family functions and the causes that may affect these functions; three functions of the family are fundamental for the living conditions and for the life quality of the families with children: the economic function, the socialization function and the function of providing emotional security. These modalities of analysis, together with the problems regarding school education, complete the perspective of analysis concerning the economic resources of the families with children and the ways of supporting them.